2017
DOI: 10.1152/physiol.00016.2017
|View full text |Cite
|
Sign up to set email alerts
|

Lactic Acid: No Longer an Inert and End-Product of Glycolysis

Abstract: For decades, lactic acid has been considered a dead-end product of glycolysis. Research in the last 20+ years has shown otherwise. Through its transporters (MCTs) and receptor (GPR81), lactic acid plays a key role in multiple cellular processes, including energy regulation, immune tolerance, memory formation, wound healing, ischemic tissue injury, and cancer growth and metastasis. We summarize key findings of lactic acid signaling, functions, and many remaining questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
186
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(190 citation statements)
references
References 156 publications
(172 reference statements)
1
186
0
3
Order By: Relevance
“…The lactate, which was also increased in the cecum of the KHK-F mice, may stimulate Nts expression in GLUTag cells. Thus, it might be the regulatory component activating Nts expression in the cecum of the KHK-F. Lactate signals though the G-protein-coupled receptor GPR81 (58) or is transported into intestinal cells by the monocarboxylate transporters (59). Expression of GPR81 in the intestine is not well documented (60).…”
Section: Discussionmentioning
confidence: 99%
“…The lactate, which was also increased in the cecum of the KHK-F mice, may stimulate Nts expression in GLUTag cells. Thus, it might be the regulatory component activating Nts expression in the cecum of the KHK-F. Lactate signals though the G-protein-coupled receptor GPR81 (58) or is transported into intestinal cells by the monocarboxylate transporters (59). Expression of GPR81 in the intestine is not well documented (60).…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Wound healing is a complex and tightly regulated inflammatory process, during which excessive inflammation leads to greater scaring. [59][60][61] High expression of TGF-β leads to excess fibroblast activity, which contributes to the development of hypertrophic scars and keloids. 51 closer, respectively, to healthy skin than that of Tegaderm.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Revascularization could be stimulated by the lactic acid supplied by the biodegradable PLGA scaffold, which has been shown to increase angiogenesis. [59][60][61] High expression of TGF-β leads to excess fibroblast activity, which contributes to the development of hypertrophic scars and keloids. The composition of collagen subtypes can also give insight into the degree of scarring that may ultimately develop in the wounds.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have confirmed that glycolysis intermediate can rapidly meet the energy requirement for cell proliferation, the material needs for fatty acids and nucleotides [9] . The glycolysis products, lactic acid also plays multiple roles in cancer processes, including energy regulation, immune tolerance, wound healing, cancer growth and metastasis [10,11] . These studies have established that glycolysis can provide favorable conditions for tumor proliferation and thus plays a pivotal role in cancer development.…”
Section: Introductionmentioning
confidence: 99%